2022
DOI: 10.7759/cureus.29100
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medical Training and Leadership at Academic Orthopedic Programs

Abstract: Introduction: When deciding on which programs to rank or fellowships to enter, medical students and residents may assess the program's prestige and specialty training opportunities. This report aimed to analyze the demographics of orthopedic department chairs and program directors (PDs), focusing on the prestige of their orthopedic training and medical school. Secondary data included fellowship, higher-level education, sex, professorship, years of practice, and total published research.Methods: We used U.S. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a more recent study, Elkadi et al found that 11.6% of program directors were female as of 2022 [ 17 ], which contrasts the results of our study of 17% of program directorship being female and the results of the Meadows et al study of 9% [ 6 ]. While this suggests an increase in female program directorship from 2020 to 2020, it is less than the percentage obtained in our investigation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, Elkadi et al found that 11.6% of program directors were female as of 2022 [ 17 ], which contrasts the results of our study of 17% of program directorship being female and the results of the Meadows et al study of 9% [ 6 ]. While this suggests an increase in female program directorship from 2020 to 2020, it is less than the percentage obtained in our investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…While this suggests an increase in female program directorship from 2020 to 2020, it is less than the percentage obtained in our investigation. We examined program directors from the top 100 programs based on reputation, while Elkadi et al assessed those from 200 orthopedic residency programs, suggesting increased female representation in program directorship at higher-ranked programs [ 17 ]. Indeed, a paper investigating the characteristics of leadership in “top-tier” orthopedic surgery residency programs supports this, as they found that higher-tier programs had a larger proportion of women leaders with statistical significance after examining 193 programs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies described the leadership in the context of Doximity rankings. To the knowledge of the authors, only one previous study looked at the relationship between orthopaedic program leadership and program ranking 18 . The study evaluated the rankings of the residency programs and medical schools in which the chairpeople, PDs, and vice chairs involved in the 2020-2021 leadership (identified N=268) trained, but it did not analyze the relationship between these leaders and their current residency programs 18 .…”
Section: Discussionmentioning
confidence: 99%
“…To the knowledge of the authors, only one previous study looked at the relationship between orthopaedic program leadership and program ranking 18 . The study evaluated the rankings of the residency programs and medical schools in which the chairpeople, PDs, and vice chairs involved in the 2020-2021 leadership (identified N=268) trained, but it did not analyze the relationship between these leaders and their current residency programs 18 . The present study is thus the first to the authors’ knowledge that evaluates characteristics of the leadership according to program ranking.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 10 years, and more profoundly in the last 5 years, the number of vice chair positions in academic orthopaedic departments has changed, from rare to quite common. However, details remain scarce, as noted in a 2022 study on orthopaedic leadership in which a comprehensive search of available public information identified only 15 orthopaedic vice chairs 5 . There is no clearinghouse with information on vice chair positions, and such information is lacking on department websites and in other resources.…”
mentioning
confidence: 99%